Integrasi Projek Penguatan Profil Pelajar Pancasila pada Shalat Dhuha di SMAN 1 Tilatang Kamang - Fajri, M.; F, Fauzan; Ilmi, Darul; N, Nurhasnah (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
In this study, initial observations at SMAN 1 Tilatang Kamang showed that the Pancasila learning profile integration project had been implemented, but only limited to theory without adequate exposure to students. The purpose of the study was to understand the problems and solutions in the integration of Pancasila learning profile, especially in Dhuha class. Field research methods were used to collect information directly, with a qualitative descriptive approach. It was found that not all students and parents attended Salat Dhuha, which affected the implementation of the project. Coordination between teaching staff and students is also needed to deepen the understanding of concepts such as the meaning of Salat Dhuha.